2014
DOI: 10.11118/actaun201462051171
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Quality and Food Safety of Regional Cheese Produced from Mixed Milk

Abstract: There were cheeses produced from raw cow's milk and from mixed milk compared. Mixed milk contained small ruminants' milk (goat's and ewe's milk) and cow's milk in diff erent proportions. There were technological, physical and health parameters, mineral composition, microbiological indicators and sensory quality evaluated. Cow's milk, compared to mixed milk, contained markedly lower amounts of fat, protein, casein, total solids, solids non fat, urea and acetone and higher values of lactose, citric acid and free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
3
0
1
Order By: Relevance
“…Moreover, Freitas and Malcata [14] made cheese from mixed goat and sheep milk in different ratios (20:80% and 40:60%) and did not find any differences in the fat content of these cheeses, while Halloumi cheese produced from mixed goat and cow milk with 25% and 50% of goat milk had a higher fat content [43]. In contrast to our research, Vyletelova-Klimešova et al [39] found that cheese produced from mixed milk (cow, sheep, and goat milk) contained more fat.…”
Section: Lećevački Cheese Compositioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Moreover, Freitas and Malcata [14] made cheese from mixed goat and sheep milk in different ratios (20:80% and 40:60%) and did not find any differences in the fat content of these cheeses, while Halloumi cheese produced from mixed goat and cow milk with 25% and 50% of goat milk had a higher fat content [43]. In contrast to our research, Vyletelova-Klimešova et al [39] found that cheese produced from mixed milk (cow, sheep, and goat milk) contained more fat.…”
Section: Lećevački Cheese Compositioncontrasting
confidence: 96%
“…Gobbetti et al [7], as well as Ponce de Leon Gonzales et al [42], concluded that hard cheese produced with mixed milk with a higher ratio of sheep milk contains a higher level of protein, which is a result of the fact that sheep milk has a higher protein content in comparison to cow milk. The obtained results are in line with those previously reported [38,39,43]. In accordance with our research, Fenelon et al [45] and Madsen and Ardo [46] reported that a decrease of fat in cheese causes moisture and proteins to increase.…”
Section: Lećevački Cheese Compositionsupporting
confidence: 93%
See 2 more Smart Citations